Research on a fuzzy adaptive state estimator for INS/GPS integrated navigation system - WANG Xin-long (Tongxin xuebao)
A fuzzy adaptive state estimator was proposed and the configuration was given,and how to use it to estimate navigation parameters and to replace the extended Kalman filtering were studied.The fuzzy adaptive state estimator was to use the Kalman filtering to configurate a fuzzy reasoning process,and to train fuzzy reasoning through neural networks,and it automatically adjusted parameters of a fuzzy system by input and output samples.Consequently,the optimum navigation parameters of the INS/GPS integrated could be estimated.The simulation results show if it to use the fuzzy logic adaptive state estimator to initial alignment of the navigation system,then the alignment time is reduced consid-erably.